1996
DOI: 10.1016/s0896-6273(00)80075-6
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Stimulation Regulates the Phenotype of Hippocampal Interneurons through the Regulation of Brain-Derived Neurotrophic Factor

Abstract: Gamma-Aminobutyric acid (GABA) switches from enhancing to repressing brain-derived neurotrophic factor (BDNF) mRNA synthesis during the maturation of hippocampal neurons in vitro. Interneurons do not produce BDNF themselves, but BDNF enhances their differentiation. Therefore, the question arose whether hippocampal interneurons regulate their phenotype by regulating BDNF expression and release from adjacent cells. The GABA(A) receptor agonist muscimol and BDNF increased the size and neuropeptide Y (NPY) immunor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
160
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(175 citation statements)
references
References 18 publications
14
160
1
Order By: Relevance
“…Finally, evidence from [ 3 H]-thymidine studies suggests that GABAergic horizontal cells might account for the apparent ability of GABA to help maintain the normal position of cone cell bodies and regulate cone synaptogenesis . In cultured hippocampal neurons, it was shown that GABA by acting on voltage gated calcium channels affects the expression of BDNF during a restricted period of the development, and this supports the hypothesis that GABA might have neurotrophic effects on embryonic or perinatal neurons (Berninger et al 1995;Marty et al 1996).…”
mentioning
confidence: 58%
“…Finally, evidence from [ 3 H]-thymidine studies suggests that GABAergic horizontal cells might account for the apparent ability of GABA to help maintain the normal position of cone cell bodies and regulate cone synaptogenesis . In cultured hippocampal neurons, it was shown that GABA by acting on voltage gated calcium channels affects the expression of BDNF during a restricted period of the development, and this supports the hypothesis that GABA might have neurotrophic effects on embryonic or perinatal neurons (Berninger et al 1995;Marty et al 1996).…”
mentioning
confidence: 58%
“…The number of GABAergic interneurons was reduced in the somatosensory and visual cortices after sensory deprivation Jones, 1986, 1988;Benevento et al, 1995). Similarly, the number of GABAergic interneurons was decreased in cortical and hippocampal cultures after activity blockade with tetrodotoxin (Marty et al, 1996;Rutherford et al, 1997).…”
Section: Activity-dependent Scaling Of Gabaergic Synapse Strengthmentioning
confidence: 98%
“…Finally, and of interest for the field of schizophrenia research, hippocampal interneurons have been shown to regulate the differentiation of hippocampal neurons during development (Marty et al 1996). That many of these functions might involve functional (and presumably structural) neuroplasticity is strongly suggested by the observation that GABA, GAD, and the GABA A receptors are all regulated in an activitydependent manner (Jones 1990(Jones , 1993.…”
Section: Functions Of Gabaergic Interneurons In the Cortex And In Thementioning
confidence: 99%